Impact of poverty on Drug Resistant Tuberculosis: A review (Research, Society and Development, 2022)
Tuberculosis (TB) is a chronic infectious disease, caused by Mycobacterium tuberculosis, responsible for the most deaths yearly worldwide. One of the greatest obstacles in its approach, according to the World Health Organization (WHO), is the rising prevalence of drug-resistant strains, leading to treatment failure and higher mortality. The objective of this study was to carry out an integrative review of the medical literature in order to identify and analyze the impact of poverty on the incidence, prevalence and effectiveness of combating drug-resistant tuberculosis. (TBDR). A systematic literature review was carried out in Pubmed, Virtual Health Library (BVS) and Scielo databases with keywords “Drug-Resistant Tuberculosis” AND “Poverty”. Included in this review were articles published in the last 10 years in Portuguese, Spanish and English available as a free full text. There was great agreement in findings not only affirming the relationship between poverty and the occurrence of TBDR but also in the mechanisms by which it affects treatment compliance, among of which were: bigger costs to access medical care, loss of income due to work absence, prejudice, discrimination and poor food intake. Social determinants still play an unequivocal role in the incidence of TB and even more in its resistant forms, with great compromise of treatment efficacy and compliance. As a result, diminishing poverty and inequality should be considered pivotal strategies against this disease, even more so than the development of new diagnostic and treatment tools.